Native T1 Mapping as an In Vivo Biomarker for the Identification of Higher-Grade Renal Cell Carcinoma: Correlation With Histopathological Findings. Issue 2 (February 2019) - Adams, Lisa C.; Ralla, Bernhard; Jurmeister, Philipp; Bressem, Keno K.; Fahlenkamp, Ute L.; Hamm, Bernd; Busch, Jonas; Makowski, Marcus R.
Abstract : Objectives: The aims of this study were to identify higher-grade clear cell renal cell carcinoma (cRCC) with native T1 mapping and to histologically correlate the results with the collagen volume fraction. Materials and Methods: For this institutional review board–approved, single-center prospective study, 68 consecutive patients received abdominal magnetic resonance imaging scans at 1.5 T between January 2017 and July 2018, using a Modified Look-Locker Inversion Recovery (MOLLI) sequence. Thirty patients with cRCC (20 men; mean age, 61.9 ± 13.1 years) who underwent partial or radical nephrectomy and histological grading according to the International Society of Urological Pathology (ISUP) classification and a separate healthy cohort of 30 individuals without renal malignancies or complex cysts (16 men; mean age, 59.7 ± 14.6 years) met the eligibility criteria. T1 values were quantitatively measured with region of interest measurements in T1 maps. Quantification of the collagen volume fraction was performed on histological sections (picrosirius red staining). Results: Native T1 values were significantly lower for lower-grade cRCC (ISUP 1 and 2) compared with higher-grade cRCC (ISUP 3 and 4; P < 0.001). A cutoff value of 1101 milliseconds distinguished higher-grade from lower-grade tumors with a sensitivity of 100% (95% confidence interval [CI], 0.69–1.00), a specificity of 85% (95% CI, 0.62–0.97), and an accuracy of 90% (95% CI, 0.73–0.98). Native T1 values were significantly associated with the histological collagen volume fraction ( P < 0.05). Furthermore, T1 times in the renal cortex, medulla, and tumor tissue showed an excellent interobserver agreement. Conclusions: Native T1 mapping could represent an in vivo biomarker for the differentiation of lower- and higher-grade cRCCs, providing incremental diagnostic value beyond qualitative magnetic resonance imaging features. Abstract : Supplemental digital content is available in the text.